Infiltrated La0.8Sr0.2Ga0.8Mg0.2O3-δ Based Cells Fed with Biogas. (2nd June 2015) - Di Bartolomeo, Elisabetta; Luisetto, Igor; Basoli, Francesco; Zurlo, Francesca; Salehi, Zahra; Licoccia, Silvia
Abstract : La0.8 Sr0.2 Ga0.8 Mg0.2 O3- d (LSGM) based porous/dense structures were optimized for infiltration of different metal catalysts. A solution of metal (Ni, Co, Cu and their 1:1 mixtures) salts was used for infiltration. Multiple infiltrations were necessary to get enough metal catalyst amount to get performing electrocatalytic performance. For the initial catalyst screening, ex-situ catalyst activity measurements were performed on impregnated LSGM powders with the same amount of metal catalyst infiltrated in the scaffolds. Electrochemical measurements were performed on infiltrated cells with the same amount of Ni and Ni-Co in the temperature range between 650 and 750°C and the results discussed and compared with catalytic measurements.